Modeling and Optimisation of Comlexity by the β-Cyclodextrin of an Organic Pollutant Model: m-Methyl Red - Chekroud, Hassina; Djazi, Fayçal; Abdelaziz, Bouhadiba; Horchani-Naifer, Karima; Rachida, Zeghdoudi; Malika, Remache (Видавництво Львівської політехніки, 2022)
Проведено моделювання адуктів β-циклодекстрину (β-CD) з м-метиловим червоним (m-MR) за допомогою параметричного методу 6 (РМ6), напівемпіричних молекулярних орбітальних розрахунків та методу натуральної орбіталі (NBO). Показано, що реакція приєднання відбувається внаслідок підтримання фіксованих координат β-CD та переміщення гостьової молекули. Різні положення між m-MR та β-CD вимірюються щодо відстані між еталонним атомом (N) гостьової молекулі та початком координат екваторіальної площини β-CD. Встановлено, що адукт m-MR/β-CD (комплекс B) має нижче негативне значення ΔG порівняно з іншим m-MR/β-CD (комплексом A), що підкреслює спонтанну поведінку процесу приєднання. Крім того, під час приєднання енергія комплексоутворення є негативною, що дає можливість стверджувати, що комплексоутворення m-MR у β-CD є термодинамічно вигідним. Встановлено, що мінімальну кількість енергії PM6 отримують в орієнтації B, а гостьова молекула частково інкапсульована в порожнині β-CD. За допомогою NBO аналізу проведено характеристику взаємодії водневих зв’язків між одинокою парою (LP(Y)) атома Y та антизв’язуючою орбіталлю (BD٭(X-H)).

Studies of cyclodextrin chemistry using quantum chemical methods are mainly adopted to investigate the formation of the inclusion complex causing changes in the physicochemical properties of the cyclodextrin guest. In this paper, we conducted a computational modeling study of the inclusion complexes of β-cyclodextrin (β-CD) with m-Methyl Red (m-MR) by using parametric method 6 (PM6), the semi empirical molecular orbital calculations and the natural bond orbital method (NBO). The inclusion process is carried out by maintaining the coordinates of the β-CD fixed and by displacing the guest molecule. The different relative positions between m-MR and β-CD are measured with respect to the distance between the reference atom (N) in the guest molecule and the origin of the coordinates from the equatorial plane of β-CD. The m-MR/β-CD (B) inclusion complex has a lower negative value of ΔG compared to another m-MR/β-CD (A) complex, highlighting the spontaneous behavior of the inclusion process. In addition, during the process of inclusion, the complexation energy is negative, which allows us to affirm that the complexation of m-MR in the β-CD is thermodynamically favorable. Among two directions A and B, the minimum energy generated from the PM6 was obtained in the orientation B and the guest molecule is partially encapsulated in the cavity of β-CD. In the NBO analysis, the stabilization energy is also usually used to characterize the hydrogen bond interaction between a lone pair (LP(Y)) of an atom Y and an anti-bonding orbital (BD٭(X-H)).
Моделювання та оптимізація складності за β-циклодекстрином моделі органічного забруднювача: метил м-червоний
Keywords: циклодекстрин; м-метиловий червоний; адукт; PM6; NBO аналіз; cyclodextrin; m-Methyl Red; inclusion complex; PM6; NBO analysis